Accumulare afflizione. Il tempo, la testimonianza e l’indicibile - Barbara Pinelli (Archivio Antropologico Mediterraneo)
Through the story of a refugee woman, this article reflects on the interplay between the memory of violence, the structures of time, and the poetics of the expressible and the reticence. What happens to these memory features when they encounter the bureaucratic and humanitarian apparatuses of asylum? These apparatuses use specific canons to trace the experience and codify the live’s events by validating mainly the violation or by posing the attention mainly on the violation. Tracing how refugee women relate to their own violation experience/trajectories and subjectivity, the article challenges the bureaucratic multiple encounters, showing how this violation is instead an accumulation of suffering. Like many other refugee stories, the story presented shows how the accumulation of suffering navigates inside and outside the social bonds and classifications that the language of state and humanitarian apparatuses struggle to code. In the eyes of these apparatuses, her ability negotiates to the social matrices of testimony and her attempt to contextualise her experience within the dimensions of the past and the future also remains invisible. The article is also an opportunity to reflect on the public recognition (given or denied) of memories of affliction related to political asylum.